The influence of sport sponsorship on brand equity - Maanda, Penelope Maserame (My University, 2019)
Sport sponsorship has become a strategic tool used globally with the objective of enhancing consumer-based equity elements. Many South Africa companies like Standard Bank are making substantial investment in sport sponsorship, however there is limited academic research assessing the ability of sponsorship to fulfil brand related objectives, particularly those relating to influence on brand equity elements. The specific aims of the study were therefore to assess whether the sport sponsorship has a positive contribution to brand equity dimension through enhanced brand awareness, brand image, brand loyalty and perceived quality. Understand the influence of sponsorship fit between event and sponsor on recall, attitudes towards the sponsor, brand loyalty and perceived quality. The research was quantitatively undertaken, using Computer Assisted Telephonic Interviews (CATI). A total of 200 respondents were interviewed for this study with 100 respondents not being aware of the abovementioned sponsor and 100 being aware of the said sponsor. The findings of the study reveal that sponsorship plays a significant and positive role in influencing on brand awareness and image, however there is no influence on brand loyalty and perceived service quality. surprisingly, the study shows that the perceived appropriate fit between the sponsor and the sport event has a negative influence on brand awareness and brand image. The implications of the results are that investment in sport sponsorship to build and enhance brand awareness and image can be a worthwhile investment. On the contrary marketers should not engage in sport sponsorship with the expectation to positively influence brand loyalty and service quality. This study makes a significant contribution in adding to the limited body of literature on this topic in South Africa and provides guidance on the effectiveness of sport sponsorship as an effective tool for building or enhancing brand equity elements.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management (Entrepreneurship and New Venture Creation) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2019